MAṢDAR ṢINĀIY DALAM KITAB AL BARZANJI KARYA SYAIKH JA’FAR AL BARZANJI (ANALISIS MORFOSINTAKSIS) (Universitas Negeri Semarang, 2022)
Maṣdar ṣināiy is an ism that includes ya' nisbat along with ta' taknits to show the nature in it. Sometimes it is formed from ism fail, ism maf'ūl, ism tafḍil, ism jāmid, ism alam, and ism maṣdar. The purpose of this study was to determine the origin of the type of maṣdar ṣināiy in the book of Al Barzanji. This research is a qualitative research with library research design. The data is in the form of maṣdar ṣināiy in the book of Al Barzanji. Data collection techniques using documentation techniques. In this study, it was found as many as 33 maṣdar ṣināiy data in the Al Barzanji book, based on the origin of the maṣdar ṣināiy type, there were 7 data from ism fāil, 2 data from ism maf'ūl, 3 data from ism alam, 19 data from ism jāmid , and 2 data came from ism maṣdar. Based on cases and grammatical markers, the researchers found 5 nominative case data with dhummah grammatical markers (vocal u), 1 accusative case data with fathah grammatical markers (vocal a), and 27 genetic case data with kasroh grammatical markers (vocal i). Based on the syntatic function, the researcher found 2 data had a syntatic function as fā’il, 4 data had a syntatic function as khobar, 5 data had a syntatic function as majrur, 11 data had a syntatic function as muḍaf ilaih, 8 data had a syntatic function as tābi’, 1 data had a syntatic function as mustatsna, 1 data had a syntatic function as maḍruf, and 1 data had a syntatic function as inna’s ism.